Antipsychotic Drug Therapies: Matching primary care practice to clinical challenges - Patricia R Hebert; Stuart Goldman; Joanna Drowos; Charles H Hennekens (Archives of Community Medicine and Public Health - Peertechz Publications, 2018)
Primary health care providers prescribe over 50 percent of drug therapies for patients with mental health issues in the United States. Nonetheless, primary health care providers tend to be reluctant to prescribe antipsychotic drug therapies despite their widespread availability and favorable benefit-to-risk ratio. This may be due, at least in part, to appropriate concerns about the serious adverse effects of all earlier first generation, or typical, as well as many of the earlier second generation, or atypical, antipsychotic drug therapies.